MEASUREMENT OF RADIONUCLIDES IN THE VICINITY OF CHASHMA NUCLEAR POWER PLANT (CNPP-1), PAKISTAN INSTITUTE OF NUCLEAR SCIENCE AND TECHNOLOGY (PINSTECH) AND OIL/GAS EXPLORATION SITES - Iqbal, Huma; Hafeez, N.; Abbas, Z.; Munir, M.; Rehman, M. S.; Mannan, A. (The Nucleus, 2011)
The radioactivity levels were investigated in the vicinity of Chashma Nuclear Power Plant (CNPP-I), PINSTECH and two oil/gas exploration sites in Chakwal by collecting and analyzing soil samples. Quantitative and qualitative analysis of the collected samples were made using Gamma Spectrometry System with the help of software win-TMCA. Radionuclides such as 232Th, 226Ra, 40K and 137Cs were found in the soil samples of CNPP-1, PINSTECH and oil/gas exploration sites. The values of mean activity concentrations of 232Th, 226Ra, 40K and 137Cs in soil samples of CNPP-I are found to be 45, 43, 547 and 2 BqKg-1 respectively; for PINSTECH these values are 37, 45, 430 and 3.5 Bqkg-1 respectively; for oil/gas site-I are 28, 29 and 468 BqKg-1 respectively (137Cs not detected at site I) and for site-II these levels are 26, 28, 441 and 1.8 BqKg-1 respectively. The activity concentration of 232Th, 226Ra and 40K in soil samples of all facilities are less than the world average value. 137Cs is much lower than several places reported around the world. Mean radium equivalent (Raeq) values are 149 BqKg-1 for CNPP-1 samples, 131 Bqkg-1 for PINSTECH, 108 Bqkg-1 for site-I and 103 Bqkg-1 for site-II. The measured radiological impact assessment factor (Raeq) is also lower than the value of 370 Bqkg-1 recommended by UNSCEAR.